AI-POWERED CONTENT MANAGEMENT SYSTEMS: A FRAMEWORK FOR AUTOMATED WEB PAGE GENERATION AND DYNAMIC CONTENT DELIVERY - Durga Rao Manchikanti (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article presents a comprehensive analysis of artificial intelligence integration within modern Content Management Systems (CMS) for automated web page generation and content delivery. The article examines the architectural framework necessary for implementing AI-driven CMS solutions, focusing on adaptive layout generation, dynamic content creation, and personalized user experiences. Through an investigation of machine learning algorithms and natural language generation techniques, this article demonstrates how AI-enhanced CMS platforms can streamline web development processes while maintaining content quality and brand consistency. The article reveals significant improvements in content delivery efficiency, user engagement metrics, and maintenance workflows across various sectors, including e-commerce and digital publishing. This article contributes to the growing body of knowledge on intelligent web systems by providing a structured approach to AI integration in content management, while addressing key challenges and considerations for practical implementation. The article concludes by outlining future directions for AI-driven CMS development and its potential impact on the web development landscape.